Transplantação de medula óssea: como é vista por doadores e doentes em Lisboa e no Recife - Silva, Maria de Fátima Patu da (2013)
This work is a doctoral research in Social Sciences and whose object of study has been the bone marrow donor/transplantation. This can be analyzed at least by two areas of knowledge: Anthropology and Medicine. We take the notion of gift as a founding concept of our reflection. Thus, we should remember the bone marrow as an object donated for transplantation that carries beyond the genetic and physiological capacity, power and strength to revive the receiver. In recent decade, organ transplantation has attracted reviews from various sectors of the Brazilian society, the media, on the other hand, has been playing an important role in the broad disclosure information by democratizing the discussions, sometimes heated and contradictory, and clarifies or raises doubts and fear in people. It is therefore a matter of great social relevance and as such has been treated well by society; it has been receptive to the calls of solidarity in organ donation as public health, because it is a procedure of high complexity and high cost, requiring measures of public policy planning and resource allocation, democratic and ethical criteria. This study aims to describe the profile of recipients of bone marrow in Recife and Lisbon. We performed a retrospective analysis from 2002 to 2010. Over this period, 134 patients underwent transplantation with unrelated donors of these, 107 in Lisbon and 26 in Recife. Patients transplanted in Lisbon (51.4 %) are female; while in Recife (69.2 %) are male. Are in the age group 0-17 years in Portugal (54.2 %) and Recife (50 %) diagnosed with Aplastic Anemia prevalent. However, in Lisbon prevailed diagnosis of Acute Myeloid Leukemia. The study draws attention to the fact that Lisbon performed more transplants in the age group of 30-39 years old (18.7%), different from Recife (11.5%) in the same age group. In terms of age group 18-29 years old showed a percentage of (15.9 %). Research has shown acute myeloid leukemia as the most prevalent disease in Lisbon. It is a fact that confirms the literature, to affect individuals of all ages, especially those in adulthood. This study is in the age group above 50 years old in Lisbon (6.5%) and Recife (3.8 %). We emphasize that in the period of data collection, Recife had a population of 1,537,704 and 2,821,699 people Lisbon. Although Recife has other units, only the center where the research was conducted was doing this type of transplant